VISUAL THINKING DAN HABITS OF STRIVING FOR ACCURACY AND PRECISION SISWAMELALUI MODEL CORE DISERTAI AKTIVITAS QUICK ON THE DRAW - Muflihatussyarifah, Muflihatussyarifah (2016)
Penelitian ini didasarkan padapermasalahan rendahnya visual thinkingdankeharusanpengembanganhabits of striving for accuracy and precision (HSAP)siswasejakdini. Visual thinking dan HSAPsangatdibutuhkantidakhanyauntukmenyelesaikanpersoalanmatematikatetapijugauntukmenyelesaikanmasalahdalamkehidupansehari-hari, sehinggadilakukan penelitian dengan menggunakan pembelajaran model CORE danpembelajaran model CORE disertaiaktivitasquick on the draw.Penelitianinibertujuan untuk menelaah peningkatan visual thinking siswa, mengkajiperbedaanpeningkatanvisual thinkingsiswaditinjaudari KAM, sertaHSAPsiswaterhadappembelajaran. Desainpenelitian yang digunakanadalahdesainkelompokkontrol non-ekivalendenganmenggunakanteknikpurposive sampling.Instrumenpenelitianberupatesvisual thinking danskalaHSAPsiswa. Hasilpenelitianmenunjukkanbahwa : (1)tidakterdapatperbedaanpencapaiandanpeningkatanvisual thinking siswa yang memperolehpembelajaran model CORE dansiswa yang memperolehpembelajaran model CORE disertaiaktivitasquick on the draw; (2) terdapatperbedaanpeningkatanvisual thinkingantarakategori KAM tinggidansedang, kategori KAM tinggidanrendah, dankategori KAM sedangdanrendah; (3) tidakterdapatperbedaanHSAPsiswa yang memperolehpembelajaran model CORE dansiswa yang memperolehpembelajaran model CORE disertai aktivitas quick on the draw.;--- The aims of this research based on the problem of lack of visual thinking and the necessity of developing habits of striving for accuracy and precision (HSAP) students since early stage. Visual thinking and HSAP is important because not only to resolve the question of mathematics, but also to solve problems in everyday life. So that CORE model learning and CORE model learning accompanied by quick on the draw activity was chosen to investigate improvement ofstudent visual thinking, examines differences visual improvement of student thinking in terms of KAM, and HSAP student towards learning. The design of this research was non-equivalent control group by using purposive sampling technique. The research instrument was a visual thinking student test and HSAP scale student. The results showed that: (1) there is no differences between achievement and improvement of visual thinking students who obtain CORE model learning and students who obtain CORE model learning accompanied by quick on the draw activity; (2) there are differences between the improvement of KAM visual thinking of high and medium categories, high and low categories, and medium and low categories; (3) there is no difference HSPA students who obtain CORE model learning and students who obtain CORE model learning accompanied by quick on the draw activity.